Beatbox sebagai Media Kreativitas Musik - Joko Widodo (Institut Seni Indonesia Denpasar, 2022)
Purpose: Beatbox is a music genre that exists in Indonesia. Beatbox as a medium for music produces and uses sound sources using the mouth. In its presentation, beatbox cannot be separated from creativity as a solo, duo, trio or quartet. This is what attracts researchers to explore beatbox and its relationship with creativity. Research methods: Researchers conducted observations and literature on beatbox and creativity through various media and literature. The research method used is qualitative using a psychological approach with beatbox and creativity as the subject. Results and discussion: As a result, beatbox as a creative medium is related to creativity indicators such as divergent, collaborative, original and flexible thinking. Implication: Creative indicators always appear in the beatbox menu in various forms.